The Concept of Anatta (Non-Self) and Its Implications for Contemporary Identity and Philosophy - Setwong, Somkid (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2025)
The concept of Anatta (Non-Self) is a cornerstone of Buddhist philosophy, fundamentally challenging conventional notions of identity and selfhood. Rooted in early Buddhist texts, Anatta argues against the existence of a permanent, unchanging self, proposing instead that identity is a dynamic and interdependent process shaped by impermanence and conditions. This paper explores the philosophical and practical implications of Anatta, examining its influence on contemporary identity, ethical behavior, and social constructs. The discussion bridges traditional Buddhist thought with modern philosophical debates, such as existentialism and postmodernism, to highlight how Anatta reshapes understandings of free will, moral responsibility, and relational identity. Furthermore, it delves into how mindfulness and meditation practices informed by Anatta contribute to psychological well-being and resilience. By integrating Anatta into therapeutic, educational, and community initiatives, the paper underscores its potential to address modern crises of identity and foster harmonious coexistence. The study concludes by advocating for a broader application of Anatta in addressing global identity challenges, emphasizing its relevance in a rapidly evolving and interconnected world.